Moran on Self-Knowledge, Agency and Responsibility - Carlos J. Moya (Crítica)
In this paper I deal with Richard Moran’s account of self-knowledge in his book Authority and Estrangement. After presenting the main lines of his account, I contend that, in spite of its novelty and interest, it may have some shortcomings. Concerning beliefs formed through deliberation, the account would seem to face problems of circularity or regress. And it looks also wanting concerning beliefs not formed in this way. I go on to suggest a diagnosis of these problems, according to which they would arise out of a view of agents too strongly dependent on the will.